Government technology support, digital finance development and corporate innovation performance - Jianmin Liu; Qin Xia (China Accounting and Finance Review)
The purpose of this study is to examine the relationship between government technology support and corporate innovation performance in the context of digital finance development. We conduct regression analyses using a sample of A-share listed companies from 2011–2022 to examine whether and how government technology support can have a positive effect on corporate innovation activities and whether digital financial development plays an incentive role in it. We find a positive relationship between government technology support and corporate innovation performance, and digital financial development has a positive moderating effect. In order to study the mechanism of government technology support and digital financial development on corporate innovation performance, this study adopts the moderated mediation effect model and finds that government technology support and digital financial development can effectively alleviate financing constraints and promote corporate innovation performance. Heterogeneity analysis shows that digital finance development has a differentiated impact on government technology support for corporate innovation performance under different property rights. Further research finds that digital financial development can better exert a positive moderating effect on government technology support and corporate innovation performance under a good internal governance and external supervision environment. This study has implications for government support for corporate innovation and development. This paper proposes policy recommendations to fully utilize government technology support and digital financial development to build internal corporate governance and external supervision mechanisms to achieve efficiency change.